The interaction of the SARS coronavirus non-structural protein 10 with the cellular oxido-reductase system causes an extensive cytopathic effect - Li, Qihan (J Clin Virol, 2005)
The pathological mechanism of SARS-CoV infection was investigated. The gene for the SARS-CoV non-structural protein 10, which is located in the open reading frame of pp1a/pp1ab gene, was synthesized and used to screen for the specific cellular gene coding for the protein interacting with this nsp10 protein in a human embryo lung cDNA library using a yeast trap method. The results indicated that apart from the two subunits of cellular RNA polymerase complex, BTF3 and ATF5, this nsp10 protein was also able to interact specifically with the NADH 4L subunit and cytochrome oxidase II. Further study revealed that the activity of the NADH-cytochrome was altered and the inner mitochondrial membrane was depolarized in the transfected human embryo lung fibroblast by the nsp10 protein gene. The cytopathic effect of the Coronavirus 229E strain appeared more extensive in these cells than in the control cells.